Case report: One case of precise resection of gastric glomus tumor by gastroscopy combined with laparoscopy - Yang, Xuan; Guo, Yunping; Yan, Xiaochen; Xu, Bin; Cui, Zhenqin; Guo, Zhuang (Frontiers in Oncology, 2025)
IntroductionGastric glomus tumor is a rare submucosal mesenchymal tumor with no distinct features on endoscopy. In clinical practice, it is often treated with laparoscopic partial gastrectomy. Here, we report a case of gastric glomus tumor successfully resected using a combination of gastroscopy and laparoscopy.Case descriptionThe patient was an elderly male who underwent gastroscopy, which revealed a submucosal mass in the gastric antrum. The lesion was suspected to be a stromal tumor. Further evaluation with computed tomography (CT) imaging indicated a space-occupying lesion in the gastric antrum, with the possibility of benign pathology. Endoscopic ultrasonography revealed that the tumor originated from the muscular layer and was approximately 28.8 mm ×22.5 mm. Blood flow was detected behind the lesion, suggesting the possibility of a gastric glomus tumor. The tumor was removed using a combination of gastroscopy and laparoscopy. Postoperative pathology suggested that it was a benign gastric glomus tumor. The patient recovered uneventfully and was discharged 7 days later.ConclusionGastric glomus tumor is a rare submucosal tumor that should be included in the differential diagnosis of gastric submucosal tumors. A combined approach using gastroscopy and laparoscopy offers a minimally invasive and effective treatment option.